Jijamata Bhonsle memorial - Ghosh, Ayan (2023)
Veermata Jijabai Bhonsle Udyan commemorates Jijabai Bhonsle (1598–1674), mother of Chhatrapati Shivaji Maharaj (1630–80) also variously known as Veermata, Rastramata, or Jijau. Jijabai taught young Shivaji about 'Swarajya' and raised him to be a great warrior and just ruler who challenged the mighty Mughal Empire and laid the foundation of the Maratha Empire.